WHEN PARIS WAS "À L'HEURE CHINOISE" OR GEORGES POMPIDOU IN CHINA AND JEAN YANNE'S (1974) LES CHINOIS À PARIS. Issue 2 (1st July 2019) - Clark, Catherine E.
Abstract : This article looks at two seemingly disparate events: Georges Pompidou's 1973 presidential visit to the People's Republic of China (PRC) and the filming and release of Jean Yanne's blockbuster comedy Les Chinois à Paris (1974). Both produced flawed visions of Franco-Chinese relations. During Pompidou's visit, officials and the press attempted to demonstrate that France enjoyed warmer relations with the PRC than any other Western nation. Yanne's film parodied the French fad for Maoism by imagining the People's Liberation Army invading and occupying Paris. His film caused an uproar in the press and sparked official Chinese protest. The article ultimately argues that the two events were deeply related, part of a wave of popular and official interest in China in the early 1970s that extended well beyond the well-known stories of student and intellectual Maoists. This interest paved the way for Franco-Chinese relations as we know them today.